2019
DOI: 10.1021/acs.oprd.8b00456
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Scalable Aerobic Oxidation by 2-Azaadamantan-2-ol (AZADOL)/NOx Catalysis: Large-Scale Preparation of Shi’s Catalyst

Abstract: A method for safe and scalable aerobic alcohol oxidation using 2-azaadamantan-2-ol (AZADOL), an azaadamantane-type hydroxylamine catalyst, with a NO x cocatalyst in a conventional batch reactor has been developed. The use of 2 mol % AZADOL and 10 mol % NaNO2 was determined to promote aerobic alcohol oxidation quantitatively within a reasonable time (8 h). Safety is ensured by controlling the reaction temperature below the flash point of the acetic acid solvent. The robustness of the developed method is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…For the time course of the oxidation of l ‐menthol ( 1 a ), 4‐Cl‐AZADO ( 7 b ) and 5‐F‐AZADO ( 4 ) had almost the same reactivity, while 4‐Cl‐AZADO ( 7 b ) has slightly improved initial reaction rate. Previous studies have reported that the use of nitroxyl radical catalysts without electron‐withdrawing groups (AZADO ( 8 ) and ABNO ( 9 )) resulted in a drastic decrease in reaction rate due to the deactivation of the catalyst caused by H 2 O [4a,5b] . 4‐Cl‐AZADO ( 7 b ) did not result in such deactivation, similar to 5‐F‐AZADO ( 4 ) and other heteroatom‐containing azaadamantane‐type nitroxyl radicals.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…For the time course of the oxidation of l ‐menthol ( 1 a ), 4‐Cl‐AZADO ( 7 b ) and 5‐F‐AZADO ( 4 ) had almost the same reactivity, while 4‐Cl‐AZADO ( 7 b ) has slightly improved initial reaction rate. Previous studies have reported that the use of nitroxyl radical catalysts without electron‐withdrawing groups (AZADO ( 8 ) and ABNO ( 9 )) resulted in a drastic decrease in reaction rate due to the deactivation of the catalyst caused by H 2 O [4a,5b] . 4‐Cl‐AZADO ( 7 b ) did not result in such deactivation, similar to 5‐F‐AZADO ( 4 ) and other heteroatom‐containing azaadamantane‐type nitroxyl radicals.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, close investigation of the role of fluorine atom in 5‐F‐AZADO ( 4 ) revealed that the fluorine atom at C5 imparts 5‐F‐AZADO ( 4 ) catalytic robustness under acidic conditions by attenuating the basicity [5b] . Although non‐substituted AZADO ( 8 ) also completed the NOx‐cocatalyzed aerobic alcohol oxidation, a larger amount of AZADO ( 8 ) was necessary to promote the reaction [4a] . This critical finding on the role of the fluorine atom on the azaadamantane skeleton led our group to synthesize a scalable surrogate for 5‐F‐AZADO ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…TEMPO, A-TEMPO, AZADOL and NHPI were purchased from Tokyo Chemical Industry Co., Ltd. (Tokyo, Japan). AZADOL is reported to be converted to AZADO by oxidation and has comparable oxidation activity for alcohols [18][19][20]. NNO [11] and Nor-AZADO [21] were synthesized according to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the same authors disclosed a scalable method for aerobic oxidation of alcohol by using nitroxyl radical catalyst 2‐azaadamantan‐2‐ol (AZADOL) and NaNO 2 as co‐catalyst (Scheme ) . In a conventional batch reactor the developed protocol oxidized diacetone fructose 108 into Shi's catalyst 109 , which is used as organocatalyst for the asymmetric epoxidation.…”
Section: Nano2‐catalyzed Oxidation Reactionsmentioning
confidence: 99%